PALAEODIETARY AND PALAEOCLIMATIC INTERPRETATIONS FOR HERBIVORE FAUNA FROM LATE PLIOCENE TO EARLY PLEISTOCENE SIWALIKS OF PAKISTAN - A. M. Khan; A. Iqbal; M. T. Waseem; R. M. Ahmad; Z. Ali (Journal of Animal and Plant Sciences, 2020)
Stable isotopes analysis of carbon and oxygen have the potential to explore the diet and climate of past communities. The end of Miocene in the Siwaliks of Pakistan marks faunal turnover due to climatic change with higher rates of aridity and an expansion of C4 grasslands. But after the Miocene, the studies regarding diet and climate of herbivore communities are still highly un-explored. We present here the analysis of δ13C and δ18O to estimate the diet and climate endeavored by herbivore communities from the Plio-Pleistocene Siwaliks of Pakistan. Our results indicate that the proportion of C3 diet in the Pliocene fauna was diminished but not absent while Pleistocene fauna do not report any evidences of C3 vegetation. The Pliocene and Pleistocene time span reports the flood plain environment with increased aridity which favored more C4 grasses from 3.6 to 0.6 Ma. We found that Pliocene and Pleistocene Siwalik faunas have close affinities with African faunal communities with respect to their dietary and ecological niche.
Keywords: Upper Siwaliks; Soan Formation; Palaeovegetation; Mammals